2020
DOI: 10.1007/s12274-020-2701-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-transforming ultrathin α-Co(OH)2 nanosheet arrays from metal-organic framework modified graphene oxide with sandwichlike structure for efficient electrocatalytic oxygen evolution

Abstract: Developing efficient and low-cost electrocatalysts for oxygen evolution reaction (OER) with high electrochemical activity and durability for diverse renewable and sustainable energy technologies remains challenging. Herein, an ultrasonic-assisted and coordination modulation strategy is developed to construct sandwich-like metal-organic framework (MOF) derived hydroxide nanosheet (NS) arrays/graphene oxide (GO) composite via one-step self-transformation route. Inducing from unsteady state, the dodecahedral ZIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 54 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…Contrastively, when WS 2 and CNTs are tightly entwined, intense charge redistribution (≈4 e nm −1 ) happens at the interface (Figure 6h), much higher than each of them. It should be noted that the electrons transfer from CNTs to WS 2 driven by the polarization effect [47,48] (Figure 6i), revealing that the built-in electric field emerges along the interfaces. The asformed electric field promotes the charge accumulation on the WS 2 , especially on the edge of 2D-WS 2 nanosheets, which is widely believed to be the active sites for electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Contrastively, when WS 2 and CNTs are tightly entwined, intense charge redistribution (≈4 e nm −1 ) happens at the interface (Figure 6h), much higher than each of them. It should be noted that the electrons transfer from CNTs to WS 2 driven by the polarization effect [47,48] (Figure 6i), revealing that the built-in electric field emerges along the interfaces. The asformed electric field promotes the charge accumulation on the WS 2 , especially on the edge of 2D-WS 2 nanosheets, which is widely believed to be the active sites for electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The deconvoluted peaks at 780.8 and 796.8 eV correspond to Co 2p 3/2 and Co 2p 1/2 , respectively, accompanied with two shake‐up satellites, which are the binding energies of Co 2+ in Co(OH) 2 . [ 38,43 ] The binding energy gap of 16.0 eV between Co 2p 3/2 and Co 2p 1/2 further confirms the existence of Co 2+ . [ 44 ] The N 1s spectra in Figure 3d can be decomposed into four peaks, which are assigned to pyridinic N (398.7 eV), pyrrolic N (399.8 eV), graphitic N (401.0 eV), and oxidized N (406.5 eV), respectively.…”
Section: Resultsmentioning
confidence: 80%
“…From the high‐resolution transmission electron microscopy (HR‐TEM) image in Figure 2e, the lattice fringes of 0.21 nm correspond to the (200) plane of CoO phase, because the cobalt hydroxide is highly sensitive to the irradiation of electron beams in TEM, and would quickly be oxidized to CoO. [ 38,39 ] The element mappings in Figure 2f further confirm the uniform growth of Co(OH) 2 nanosheets on NC nanoflake arrays. The morphology of control samples of 1 h‐Co(OH) 2 @NC and 12 h‐Co(OH) 2 @NC are shown in Figure S2 (Supporting Information), from which we can conclude that the size of Co(OH) 2 nanosheets increases with the reaction times.…”
Section: Resultsmentioning
confidence: 95%
“…[ 122–125 ] Hence, designing MOF composites together with desired conductive polymers or carbon is promising to construct ideal cathode frameworks and deliver a large discharge capacity. [ 126,127 ] Notably, the Cui group concluded that the conductivity of the common conductive polymers, [ 128 ] like polyaniline (denote PANI), polypyrrole (denote PPY), and poly(3,4‐ethylenedioxythiophene) (denote PEDOT), increased as follows: PANI < PPY < PEDOT, suggesting that the PEDOT possess the best conductivity. Therefore, exploiting potential MOF composites with PEDOT could lead to high conductivity, thus promoting low internal resistance and fast electron migration.…”
Section: Enhancing the Conductivity Of Mof‐derived Nanostructuresmentioning
confidence: 99%